2016
DOI: 10.3895/rbta.v10n1.2072
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento De Caldo De Cana Pasteurizado Adicionado De Frutas Ácidas

Abstract: A adição de concentrados de frutas ácidas ao caldo de cana pode ser uma opção para o consumidor no mercado alimentício de novos produtos. Neste contexto, objetivou-se desenvolver duas diferentes formulações de caldo de cana pasteurizado, adicionado de suco concentrado de limão ou maracujá. Foram realizados testes preliminares, com adição de 5%, 7,5% ou 10% do suco concentrado da fruta (limão ou maracujá) ao caldo de cana. Foi aplicado o teste de ordenação-preferência para cada grupo de amostras referentes ao s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
3
2
1
Order By: Relevance
“…Titratable acidity results for raw juice greater that those found in this work (0.1% and 0.2%) were reported by Saxena et al and Sanda et al respectively.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Titratable acidity results for raw juice greater that those found in this work (0.1% and 0.2%) were reported by Saxena et al and Sanda et al respectively.…”
Section: Resultssupporting
confidence: 55%
“…In a study by Ramachandran et al on the optimization of cane juice's shelf life, the pH value was 5.2. Sanda et al reported a pH of 5.28. These results are similar to those from this study.…”
Section: Resultsmentioning
confidence: 99%
“…reported acidity of 0.2% citric acid in fresh cane juice, andChauhan et al (2002) observed acidity in the range of 0.24%-0.39% for the juice extracted from different cultivars Saxena et al (2016). andSanda et al (2016), respectively, reported results for raw juice of 0.1 and 0.2%, which were near to those herein found.TA B L E 1 Physicochemical parameters of cane juice extracted from the cultivar RB867515…”
supporting
confidence: 83%
“…In a study conducted by Ramachandran, Sudha Rani, Lavanya, Nivetha, and Usha (2016), addressing the shelf life optimization of cane juice, the pH found for the raw juice was 5.2. In another study, the reported pH was 5.28 (Sanda, Silva, Silva, & Orsine, 2016). These results are similar to those presented in this study.…”
Section: Resultsmentioning
confidence: 95%
“…Oliveira et al (2007) evaluated sugarcane juice in natura and found total reducing sugars and ascorbic acid contents of 17.68 g/100 g sucrose and 2.98 mg/100 mL respectively, which is close to the present study, with values of 8.11 g/100 g sucrose and 2.81 mg/100 mL, respectively. The turbidity and acidity values of the samples of the present study were 163 NTU and 98.00 mg citric acid/100 mL, respectively, while Prati (2010) and Sanda (2016) found 87.80 NTU and 41.00 mg citric acid/100 mL, respectively, in sugarcane juice in natura.…”
Section: Physicochemical Characterization Of Pasteurized Sugarcane Juicecontrasting
confidence: 45%